MAKNA PESAN TATO SEBAGAI BENTUK IDENTITAS DIRI DI KALANGAN PENGGUNA TATO DI KOMUNITAS RIAU TATTO COMMUNITY (RTC) - Fadel Muhammad; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tattoo is a symbol work of art. Meanings of the symbols is an integral part and the interaction of different communication patterns of thought and action which later became the deal. The phenomenon of tattoo is not born out of a tube called modern world and urban. Historically, tattoos were born and come from inland culture, traditional, even old-fashioned can be said. Community tattoo in Pekanbaru from the largest tattoo community in Indonesia Indonesian Subculture: Riau Tatto Community (RTC), which was established in April 2013. The community is comprised of 28 and 8 of them are tatto maker (tatto maker) who has his own tattoo studio and chaired by Buntala and regulars they called lovers of tattoos (tattoo lover). This study aims to determine the meaning of a message tattooed as a representation, interpretation and object identity among users in Riau tattoo Tatto Community.This study uses qualitative research methods to perform the method of semiotic analysis approach. Subjects in this study is the chairman of RTC along with five members of the secretariat who have a tattoo studio (tattoo maker) and members who do not have a tattoo studio (tattoo lover) each - each representing the five classifications of tattoos determined through purposive sampling technique. Data collected by observation, interview, and documentation. Data were analyzed using the phenomenological research data analysis according to Creswell. Mechanical examination of the validity of data through triangulation.The results of this study indicate that the meaning of a message tattooed as a representation of identity among the tattoo community RTC, ie the tattoo community RTC showed their understanding of art appreciation, actualization representing self-identity users multiple tattoos background meaning that formed in the pictures tattoo. the meaning of the message of tattoos as an interpretation of identity among the tattoo community RTC, the variety of tattoo designs are multi interpretation because the tattoo is something very symbolic to show the values of interpretation that refer to their previous understanding of the various symbols that have been or associate in the local culture. meaning tattoos messages as objects of identity among the tattoo community RTC, the tattoo can show a very personal side of the tattoo as well as the meaning of the images used and motivation in making these tattoos.Keyword: Message meaning, Tatto, Self-Identity, Community.